Ethical Challenges With Deactivation of Durable Mechanical Circulatory Support at the End of Life: Left Ventricular Assist Devices and Total Artificial Hearts. (January 2014) - Rady, Mohamed Y.; Verheijde, Joseph L.
Left ventricular assist devices (LVADs) and total artificial hearts (TAHs) are surgically implanted as permanent treatment of unrecoverable heart failure. Both LVADs and TAHs are durable mechanical circulatory support (MCS) devices that can prolong patient survival but also alter end-of-life trajectory. The permissibility of discontinuing assisted circulation is controversial because device deactivation is a life-ending intervention. Durable MCS is intended to successfully replace native physiological functions in heart disease. We posit that the presence of new lethal pathophysiology (ie, a self-perpetuating cascade of abnormal physiological processes causing death) is a central element in evaluating the permissibility of deactivating an LVAD or a TAH. Consensual discontinuation of durable MCS is equivalent with allowing natural death when there is an onset of new lethal pathophysiology that is unrelated to the physiological functions replaced by an LVAD or a TAH. Examples of such lethal conditions include irreversible coma, circulatory shock, overwhelming infections, multiple organ failure, refractory hypoxia, or catastrophic device failure. In all other situations, deactivating the LVAD/TAH is itself the lethal pathophysiology and the proximate cause of death. We postulate that the onset of new lethal pathophysiology is the determinant factor in judging the permissibility of the life-ending discontinuation of a durable MCS.